CRITICAL ANALYSIS OF RELIGIOUS REASON AND POSITIVE LAW IN MARRIAGE DISPENSATION DECISION - Ridwan Fariz Maulana; Rachmi Sulistyarini; Siti Rohmah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to uncover how religious interpretation and legal practice influence each other and to what extent this influence hinders or encourages the protection of children's and women's rights. This study utilizes library research focused on integrative literature analysis by combining various theories. The results suggest that the normalization of marriage dispensation reveals a fundamental paradox between religious reasoning and positive law that fails to meet within the humanitarian horizon, where religion is trapped in a morality that justifies patriarchy and the law loses its critical power due to submission to social pressures and conservative interpretations. In this situation, judges, as dual interpreters, often mediate between faith and the constitution pragmatically, so that legal decisions turn into pseudo-moral legitimations that actually negate the principle of child protection. This phenomenon not only marks normative tensions but also demonstrates an epistemological crisis in which religion and law have both lost their prophetic function as liberating forces, and therefore demands a reconstruction of reason that places substantive justice and human dignity above texts, traditions, and the fear of sin.